Implications of the Noodweer Excess Approach in Excessive Self-Defense with the Integration of Philosophy and Law - Safira Ila Mardhatillah; M. Nurul Huda; Rido Idham (Universitas Islam Negeri Walisongo Semarang, 2024)
This article discusses the case of Noodweer Excess, which is referred to as an emergency defense that exceeds the limits as regulated in Article 49, paragraph (2) of the Criminal Code. However, in reality, there are cases of Noodweer Excess that have caused someone's death. Then, this research attempts to discuss and explore how a philosophical perspective can answer and explain complex legal problems. The primary focus of this article's research is how philosophical and legal theories, such as the theory of justice and ethics, can explain the meaning and implications of an emergency defense that exceeds the limits. By integrating legal and philosophical theories, this article aims to provide a deeper and more comprehensive understanding of the case, compared to using only one area of ​​legal approach. This research serves as a bridge between legal and philosophical studies and offers broader insights. Thus, this article provides a more complete perspective on how Noodweer Excess or an emergency defense that exceeds the limits as regulated in Article 49 paragraph (2) of the Criminal Code can be handled and decided fairly and ethically from the perspective of legal and philosophical theories. Artikel ini membahas tentang kasus Noodweer Excess yang disebut sebagai pembelaan darurat yang melampaui batas sebagaimana diatur dalam Pasal 49 ayat (2) KUHP. Namun pada kenyataannya, terdapat kasus Noodweer Excess yang mengakibatkan kematian seseorang. Kemudian, penelitian ini mencoba membahas dan mengeksplorasi bagaimana perspektif filsafat dapat menjawab dan menjelaskan permasalahan hukum yang kompleks. Fokus utama penelitian artikel ini adalah bagaimana teori filsafat dan hukum, seperti teori keadilan dan etika, dapat menjelaskan makna dan implikasi dari pembelaan darurat yang melampaui batas. Dengan memadukan teori hukum dan filsafat, artikel ini bertujuan untuk memberikan pemahaman yang lebih mendalam dan komprehensif terhadap kasus tersebut, dibandingkan jika hanya menggunakan satu bidang pendekatan hukum. Penelitian ini berfungsi sebagai jembatan antara kajian hukum dan filsafat serta menawarkan wawasan yang lebih luas. Dengan demikian, tulisan ini memberikan sudut pandang yang lebih lengkap tentang bagaimana Noodweer Excess atau pembelaan darurat yang melampaui batas sebagaimana diatur dalam Pasal 49 ayat (2) KUHP dapat ditangani dan diputus secara adil dan etis dari perspektif teori hukum dan filsafat.